(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This study aimed to analyze the impact of water quality on living beings especially on aquatic life and those who use it for drinking purposes. The preliminary analysis of the data showed that water quality indexes are rising year to year in wular lake. Further, the analysis showed that the water quality parameters are more effective to aquatic life ,because the aquatic life needs more water for living.The main areas which are polluting the water are industries,using of fertilizer and pesticides also use of chemicals in paints. Similarly, the waste water of villages and towns is less effecting in increasing the water indexes as compared to the industrial waste water.The main pollutants are dying industries,use of unwanted medicines in plants are causing sevier problems in water. During construction usage of oils also cause these problems in increasing the water quality parameters. The water of the lakes are getting effected due to these wastes , because the wular lake is the main fresh water lake in Kashmir india. Maximum people of valley are using it in drinking purposes. They are getting effected by this unclen water. Due to this the chest prolems are created due to which the water of wular lake had became the main problem causing agent in population. Results are showing the bad effect on population and aquatic life,because the aqualtic species are indirectlt effectin on humans. By eating fishes and nuts of wular lake. Based on these results, we conclude that reduction in water quality parameters is a major concern because day by day the industries are increasing the waste and it is directly effective in increasing the parameters , government should to take immidate steps to save this fresh water lake. As a result, the government should devise strategies to reduce harmful water quality parameters which are causing main effect to living population. Environmental protection is a long process requiring ongoing planning, government regulations, and public and industrial participation. To decrease these parameters everyone should be involved in this matter, it is abig concern future generation.